Leading matters! Linking compassion and mindfulness in organizations through servant leadership - Miralles, Sandra; Pessi, Anne B.; Pozo-Hidalgo, Manuela; Rodríguez-Sánchez, Alma (Frontiers in Psychology, 2024)
Regardless of where they are, humans are inherently human. In this study, we explore the relationship between compassion, mindfulness, and servant leadership contributing to an overall feeling of safety. Adopting a humanistic approach to human resource management, we examine how compassion and mindfulness intersect under the lens of the Conservation of Resources (COR) theory. Our investigation focuses on understanding how servant leadership facilitates the cultivation of mindfulness through compassion. Using structural equation modeling (SEM), we analyze data gathered from 360 workers across diverse occupational sectors. Our findings provide empirical support for the hypothesis that compassion, manifested as a response to suffering, enhances mindfulness levels in the workplace. Specifically, we observe that organizations promoting servant leadership principles are conducive to higher levels of mindfulness among employees. Practically, our study underscores the importance of designing work contexts that prioritize compassion and servant leadership. By doing so, organizations can foster a positive work environment that promotes mindfulness and enhances workplace safety. Our research contributes to the management literature by offering empirical evidence on the role of servant leadership in cultivating compassion and mindfulness, thereby advancing the discourse on workplace safety and organizational well-being.